Impacto de la cartera vencida y su incidencia en la ejecución del presupuesto del Gobierno Autónomo Descentralizado Municipal de Chambo en el periodo 2024. - Solis Cuadrado, Valeria Mishell (2025)
The failure of taxpayers to fulfill their tax obligations has a direct impact on the ability of municipalities to implement their budgets, thereby hindering the delivery of services and programs intended to benefit citizens. For the Decentralized Autonomous Municipal Government of Chambo, the overdue portfolio functions as a constraint on the efficient and effective execution of the budget. The objective of this research was to determine the impact of overdue portfolios and their incidence on the execution of the budget of the Decentralized Autonomous Municipal Government of Chambo in 2024. The present study employs a mixed-methods approach, incorporating a non-experimental design, integrating field and documentary research, and adopting a descriptive level of analysis. A variety of instruments were employed in the research process, including surveys of officials from the financial department of the GADM Chambo and an interview with the financial director. A thorough analysis of the available data reveals a clear correlation between the overdue portfolio and budget execution. Furthermore, the analysis uncovers a significant impact of tax culture on the overdue portfolio. Through the implementation of a correlation analysis, it was ascertained that an increase in the overdue portfolio was concomitant with a rise in the complexity of budget execution. Consequently, a series of strategies was put forth as potential solutions for the institution to address the overdue portfolio.